Part A
y varies directly with x, so we know that y = kx for some constant k. Why the letter 'c' isn't used as a constant, instead of k, I'm not entirely sure.
We're told that x = 0.5 and y = 36. Let's use those values to find k
y = kx
36 = k*0.5
36/0.5 = k
72 = k
k = 72
The equation y = kx updates to y = 72x
As a check, plug x = 0.5 in to get,
y = 72x
y = 72*0.5
y = 36
which helps show that we have the correct equation.
Answer: y = 72x
===============================================================
Part B
If y = 1/3, then,
y = 72x
1/3 = 72x
72x = 1/3
x = (1/3)*(1/72)
x = (1*1)/(3*72)
x = 1/216
Note how I multiplied both sides by 1/72, which is the same as dividing both sides by 72.
Answer: x = 1/216